RETRACTED: Ecosystems in the financial environment as a digitalization trend - Tretyakova Irina; Kolmykova Tatiana; Serebryakova Nadezhda; Astapenko Elena; Kotsyurko Elena (E3S Web of Conferences, 2024)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001